ANALISIS DETERMINAN MINAT WIRAUSAHA PEMUDA DI KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Ilham Mirzaya Putra (Quantitative Economics Journal, 2017)
The objectives of this research were to determine: 1) the interest of young entrepreneurs in the district of Percut Sei Tuan, Deli Serdang Regency. 2) the influence of youth personalities, environment, and demography towards the interest of youth Entrepreneurship in the district of Percut Sei Tuan, Deli Serdang regency. Techniques used in the sampling was Franc Lynch. Research samples were taken from the youth in the district of Percut Sei Tuan aged from 18-30 years old, with 96 respondents obtained randomly. Data collection techniques used was primary, using questionnaires and a Likert scale on each question. The research method used was a survey. While for the data analysis technique a descriptive test and multiple linear regression were used. The result of thisresearch revealed that: 1) Interest entrepreneurial youths in the district of Percut Sei Tuan in Deli Serdang area is very positive 2) Self efficacy, Achievement Needs, Availability Information, Networking, Access to Capital, and Demographics positively related to interest youth entrepreneurship in the district Percut Sei Tuan, Deli Serdang Regency. 3) Self efficacy, Achievement Needs, Availability Information, Networking, Access to Capital, and Demographics simultaneously significant effect on variable interest in youth entrepreneurship in the district Percut Sei Tuan, Deli Serdang Regency 4) Self efficacy, Achievement Needs, Availability Information, Networking, and Access to Capital partially no significant effect on variable interest in youth entrepreneurship in the district Percut Sei Tuan, Deli Serdang Regency. 5) Demographics partially have significant effect on variable of variable interest in youth entrepreneurship in the district Percut Sei Tuan, Deli Serdang Regency.